Newborns' neural processing of native vowels reveals directional asymmetries - Chládková, Kateřina; Urbanec, Josef; Skálová, Sylva; Kremláček, Jan (Developmental cognitive neuroscience, 2021)
Prenatal learning of speech rhythm and melody is well documented. Much less is known about the earliest acquisition of segmental speech categories. We tested whether newborn infants perceive native vowels, but not nonspeech sounds, through some existing (proto-)categories, and whether they do so more robustly for some vowels than for others. Sensory event-related potentials (ERP), and mismatch responses (MMR), were obtained from 104 neonates acquiring Czech. The ERPs elicited by vowels were larger than the ERPs to nonspeech sounds, and reflected the differences between the individual vowel categories. The MMRs to changes in vowels but not in nonspeech sounds revealed left-lateralized asymmetrical processing patterns: a change from a focal [a] to a nonfocal [ɛ], and the change from short [ɛ] to long [ɛ:] elicited more negative MMR responses than reverse changes. Contrary to predictions, we did not find evidence of a developmental advantage for vowel length contrasts (supposedly most readily available in utero) over vowel quality contrasts (supposedly less salient in utero). An explanation for these asymmetries in terms of differential degree of prior phonetic warping of speech sounds is proposed. Future studies with newborns with different language backgrounds should test whether the prenatal learning scenario proposed here is plausible.
Keywords: Newborn ERP; novorozenec; Infant, Newborn; Infant; Humans; Pregnancy; Speech sound acquisition; Category formation; kojenec; evokované potenciály; řeč; Speech Perception; fonetika; Female; percepce řeči; Phonetics; Speech; lidé; elektroencefalografie; Prenatal learning; ženské pohlaví; Evoked Potentials; těhotenství; Language development; Electroencephalography